PENGEMBANGAN LKPD BERBASIS MODEL PJBL-STEM TERINTEGRASI KARAKTERISTIK ENTREPRENEUR BERORIENTASI TERHADAP KETERAMPILAN BERPIKIR KREATIF PESERTA DIDIK - Afrijhon, Novia Sari; Sutrisno, Sutrisno; Maison, Maison (EduFisika: Jurnal Pendidikan Fisika, 2022)
The purpose of this development research is to produce worksheet products based on the integrated PjBL-STEM model with entrepreneurial characteristics oriented towards the creative thinking skills of students in the material of heat and its transfer. This research is a type of development research (Research and Development) using the ADDIE model. The LKPD teaching materials that had been developed were then validated by a team of experts, and then tested on class VII students at SMP N 12 Jambi City. The subjects of this research trial were science teachers, one-on-one and small group trials. From the analysis of the assessment of the two teachers, a percentage of 90% was obtained with the "very good" category, to see the agreement of the two teachers, a kappa test was also carried out with a value of 0.820 in the "very good" category. In the one-on-one test conducted on three students, it was found that the overall average percentage was 83.3% in the "very decent" category. After the one-on-one trials, small group trials were also carried out on six students and it was found that the overall average percentage was 85%.